ChemInform Abstract: One‐Pot Synthesis of Benzopyran‐4‐ones with Cancer Preventive and Therapeutic Potential. Issue 27 (16th June 2016) - Talhi, Oualid; et al.,
Abstract: The title benzopyranones are prepared by a tandem sequence involving the organobase‐catalyzed Michael addition of R 1 COCH2 COR 2 to chromonecarboxylic acid leading to decarboxylation followed by a Baker—Venkataraman rearrangement of the resulting Michael—adducts via chromone‐ and/or chromanone ring closure when R 1 is an ortho‐hydroxyaryl group.